Effects of Dual Peroxisome Proliferator-Activated Receptors α and γ Activation in Two Rat Models of Neuropathic Pain. (17th April 2019) - Alsalem, Mohammad; Haddad, Mansour; Aldossary, Sara A.; Kalbouneh, Heba; Azab, Belal; Dweik, Aala; Imraish, Amer; El-Salem, Khalid
Abstract : Neuropathic pain is a growing healthcare problem causing a global burden. Currently used analgesics such as opioids are associated with adverse effects; urging the need for safer alternatives. Here we aimed to investigate the potential analgesic effects of tesaglitazar; dual peroxisome proliferator-activated receptors α and γ (PPAR α and γ ) agonist in rat models of neuropathic pain. This study also aimed to investigate the modulation of the transient receptor potential vanilloid 1 (TRPV1) receptor activity by tesaglitazar which could provide a potential mechanism that underlie tesaglitazar antinociceptive effects. Von Frey filaments were used to determine the paw withdrawal threshold (PWT) in adult male Sprague Dawley rats (180-250g) following i.p. injection of streptozotocin (STZ) or cisplatin, which were used as models of neuropathic pain. Antinociceptive effects of tesaglitazar were determined 6 hours after drug administration. Cobalt influx assays in cultured dorsal root ganglia (DRG) neurons were used to study the effects of tesaglitazar preincubation on capsaicin-evoked cobalt influx. Both cisplatin and STZ produced a significant decrease in PWT. The higher dose of tesaglitazar (20 μ g/kg) significantly restored PWT in both neuropathic pain models (P<0.05). 10 μ M capsaicin produced a robust cobalt response in DRG neurons. Preincubation of DRG neurones with tesaglitazar 6 hours prior to stimulation with capsaicin significantly reduce capsaicin-evoked cobalt responses in a PPAR α and PPAR γ dependent fashion (P<0.05). In conclusion, tesaglitazar produced significant analgesic effects in STZ and cisplatin-induced neuropathy, possibly by modulating TRPV1 receptor activity. This may be of potential benefit in clinical practice dealing with peripheral neuropathy.